PENGARUH PENAGIHAN PAJAK DENGAN SURAT TEGURAN DAN SURAT PAKSA TERHADAP EFKTIVITAS PENCAIRAN TUNGGAKAN PAJAK (Studi Kasus KPP Pratama Bandung Karees Periode 2010-2013) - Diah Putri Pertiwi (Bina Ekonomi, 2014)
The amountof taxarrearsis increasingdue to thetaxpayerdoes notpay offthe taxdebts. Tax debt that has not been repaid by taxpayer is oftenencounteredbecausethe increaseof tax arrearswere still not balanced bydisbursementactivities. Tax arrears that rises cause target disbursement arrears tax rising too.One way to disburse tax arrears and reach the target was with the activities of tax collection by letterof reprimand and forced letter. This research aims to know the influence of tax collection with a letter of reprimand and forced letter to the effectiveness oftax arrears disbursementPopulation and sample of this research are a number of letter of reprimand, a number of forced letter, and reports of the target and the realization of tax arrears disbursement of every quarter at KPP Pratama Bandung Karees in year 2010-2013. The processed data is the primary data taken directly by the authors. This data is then analyzed by using multiple linear regression analysis, having previously done a classic assumption test. Hyphotheses test that this research use are partial and simultaneous. This research result indicates that collection tax by warning letter and force letter, both in simultaneous or partial did not influence significantly to the effectiveness of the disbursement of tax arrears.